Case Report: A case of borderline lepromatous leprosy and literature review—key clues to expand clinical diagnostic thinking - Lu, Li; Wang, Lei; Wei, Kui; Wei, Xian-wen; Hua, Ying-jian (Frontiers in Medicine, 2025)
BackgroundLeprosy, also known as Hansen’s disease, is a chronic infectious disease caused by Mycobacterium leprae. It primarily affects the skin, peripheral nerves, mucous membranes, and the eyes. If left untreated, it can lead to severe nerve damage, deformities, and permanent disabilities. According to a report by the World Health Organization in 2023, there were approximately 180,000 new cases globally. From 2014 to 2023, the total number of new cases worldwide decreased by 14.6%. Although certain achievements have been made in the prevention and control of leprosy, there are still deep-rooted misunderstandings and prejudices regarding leprosy in society. Consequently, patients and their families suffer from discrimination and exclusion in many aspects of life, making it difficult for them to truly integrate into society.Case presentationA 52-year-old Dai pepole woman presented with the chief complaints of “generalized edema for 6 months and erythema and numbness of the hands and feet for 3 months.” Through histopathological examination, acid-fast staining, and Bacterial Index (BI) testing, she was diagnosed with borderline lepromatous leprosy. She was administered a multi-bacillary multidrug therapy (MDT-MB) regimen for anti-leprosy treatment.ConclusionWe report a case of borderline lepromatous leprosy with generalized swelling as the initial symptom and review and analyze misdiagnosed and rare cases reported in the literature. The aim is to provide clinicians with more diagnostic ideas and reference bases and to promote the further development of leprosy prevention and control work.